SIMULASI PERSEDIAAN JAGUNG PADA PERUSAHAAN PAKAN TERNAK DENGAN PENDEKATAN SISTEM DINAMIS ( Studi Kasus di PT. Charoen Pokhpand Indonesia ) - , M. ABDILLAH ALKAFI, Ibnu Wahid Fakhrudin Aziz, STP, MT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fluctuations in supply will cause instability of inventory. It result to increase possibility of unfulfilled demand. So it is necessary to make inventory adjustments to consumer demand in achieving a high level of service . Study was conducted by identifying the basic system of maize supply chain focused on corn feedstock supply company . Furthermore is modelling supply chain system with a dynamic software system Powersim Studio 9 Express and then performed validation . Simulation is performed to determine initial conditions of supply and demand . The final stage is to perform simulation scenario 1 and 2 to see changes in system conditions . Maize supply chain system is divided into three subsystems , namely subsystem suppliers of raw materials , industrial subsystems , and consumer subsystems . Fluctuations in supply conditions resulted in company less responsive to meet consumer demand as indicated by demand 894.45 tons / day and supply 712.33 tons / day . Potential increase in demand by 10 % pushing PT . CPI Semarang to increase inventory by 11 % with 1% increase in total costs . In scenario 2 , increased in demand by 15% followed by 10% increase of order cost that affect total cost rose by 10 % and increase supply by 16 % .